Sri Lanka Paradise Lost, Paradise Regained - Naseby, Michael (London Unicorn, 2020)
"Both a comprehensive survey of the cultural, political, military, and social landscape of the country and a highly personal account of Naseby's experience. I would urge anyone thinking of visiting Sri Lanka to take this book as a travelling companion; but more widely, anyone with an interest in the Indian sub-continent will greatly enjoy the read."--Jonathon Riley, author of Ghosts of Old Companions "Naseby has been a long-standing friend to Sri Lanka. Having worked there in the 1960s and been a regular visitor and advocate of this complicated and magical island ever since, few understand the country as he does and it is wonderfully captured in this book."--Rt. Hon Lord Jonathan Peter Marland
Includes Index
Keywords: Naseby, Michael Morris, -- Baron; Sri Lanka -- Politics and government -- 1978-; Sri Lanka -- Travel; Biography